2012
DOI: 10.1259/bjr/96070557
|View full text |Cite
|
Sign up to set email alerts
|

The economic implications of unsuspected findings from CT urography performed for haematuria

Abstract: Objectives: We set out to determine the prevalence of unsuspected findings from CT urography (CTU) performed for haematuria and to evaluate the economic implications associated with the subsequent management of these findings. Methods: We analysed the results of 778 consecutive CTU scans performed in a haematuria clinic between 2008 and 2010. We excluded cases where diagnosis of an abnormality had been made prior to CTU. Costs incurred during the follow-up of unsuspected findings were calculated following guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…CTU is a more expensive examination [18] and involves a higher radiation exposure to the patient [19]. Additional concerns regarding the use of CTU include potential nephrotoxic or allergic adverse reactions to IV contrast material and the cost and potential morbidity related to incidental findings [20,21]. Patients with hematuria who have under-H ematuria is a common problem, affecting 0.…”
mentioning
confidence: 99%
“…CTU is a more expensive examination [18] and involves a higher radiation exposure to the patient [19]. Additional concerns regarding the use of CTU include potential nephrotoxic or allergic adverse reactions to IV contrast material and the cost and potential morbidity related to incidental findings [20,21]. Patients with hematuria who have under-H ematuria is a common problem, affecting 0.…”
mentioning
confidence: 99%
“…Again, this is similar to previous studies, which reported such findings in 11%-15% of their patient population. [9][10][11] The similarity between results is interesting, considering that each study used different classifications of clinical importance for incidental findings. Whereas no standard classification system exists for CTU incidental findings, many of these studies are based on systems used in studies evaluating incidental extracolonic findings on CT colonography.…”
Section: Discussionmentioning
confidence: 90%
“…5,7 The use of CTU also commonly reveals incidental extraurinary findings of which a small number are clinically significant. [9][10][11][12] This may lead to additional and ultimately negative workups. 11 Previous studies have evaluated the costs of incidental CTU findings in the evaluation of gross hematuria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Cauberg et al 30 over one in four patients undergoing a CTU for haematuria had an incidentaloma, with 14.4% being life threatening. The economic cost to the NHS in the study by Bromage et al 31 was £60 per incidentaloma. In our opinion poll 62% of clinicians felt that CTU should be the first line investigation for VH with just over half surveyed feeling unconcerned by its implementation in haematuria clinics.…”
Section: Discussionmentioning
confidence: 94%